Evaluation of Drug Prescription Patterns and Interactions in a Tertiary Teaching Hospital in Kerman, Iran: Drug pattern prescription and interaction in tertiary hospital - Sepehri, Gholamreza; Shamsi Meymandi, Manzumeh; Afsharmanesh, Armin; Sadeghi, Siavash (Iranian Journal of Pharmaceutical Sciences, 2024)
The rational use of drugs is a priority in health policy. Limited studies have been conducted about drug consumption in hospitals. Therefore, we evaluated the pattern of prescription and drug-drug interactions in cardiovascular and gastrointestinal wards. This retrospective study was conducted in a tertiary teaching hospital in Kerman. Data included demographic information and indicators such as type, category, and drug administration route. Diagnosis, outcome, and hospitalization days were other data extracted from the registered patients’‌ information. An online interaction checker of Drug.com (IBM Micromedex) was used to detect drug interactions. Analysis was computed using SPSS V22. Our findings showed that 50.7% of the patients were male in the gastroenterology ward, and 49.3% were female. Patients aged 59±0.7 years and days of hospitalization ranged between 2 to 18 days. Proton pump inhibitors (PPIs) as pantoprazole (28.4%), antibiotics (23.3%) as ceftriaxone, metronidazole and anticoagulant (21.7%) as heparin were the most prescribed drug categories in gastroenterology ward. In the cardiovascular ward, 41.6% of the patients were male and 58.4% female, aged 57±1 years, and days of hospitalization ranged between 3 to 12 days. Anticoagulants/antiplatelets (29.1%), PPIs (13.8%), statins (11.9%), and beta blockers (10.7%) were the most prescribed drug categories in cardiovascular wards. No major drug interaction was seen in gastroenterology inpatients, but major interactions, mainly due to clopidogrel administration, were observed in 11% of cardiovascular ward inpatients. The pattern of drug prescription was based on diagnosis. No correlation was found between drug interaction with diagnosis, outcome, and sex in any of the departments, but a significant correlation was found between drug interaction with patients’ age. In conclusion, appropriate prescribing of drugs based on diagnosis was seen in both wards. The pattern of drug use was rational and comparable to similar documents. Also, lower potential drug interactions could be considered as a notable result.